Class Struggle in Maze Runner: The Death Cure Film - Leandra Nur Ariefka; Sholikatus Sa'diyah (LITTERATURA: Jurnal Bahasa dan Sastra, 2022)
This research analyzes how class struggle happened in the film: Maze Runner: The Death Cure. This study uses the qualitative method, which aims to understand the phenomenon experienced by the subject of the research, such as behavior, perception, and action. The author collects data for research taken from screenshots of several scenes related to analysis and the film's dialogue. The utilized theories in this research are Marxism, and the writer explained in detail the class social, both the bourgeoisie and proletarian, that can cause the conflict in the film based on Marxism Theory. The result of this research shows how class struggle that happened in the film with the problem of social class in this film that is an exploitation of the upper classes (bourgeoisie), namely the organization named WICKED, by the lower classes (proletariat), namely the youth and society who never get justice. Therefore, there was a rebellion movement from young people and the community (proletariat) to fight for their social status.